Molecular ecology of foodborne pathogens in primary production agriculture environments in northern Colorado and investigations in internalin A diversity in Listeria monocytogenes DUP-1039C strains - Manuel, Clyde Simmons, author; Nightingale, Kendra, advisor; Goodridge, Lawrence, committee member; Avens, John, committee member; Bunning, Marisa, committee member (Colorado State University. Libraries, 2011)
Listeria monocytogenes, Salmonella, and Shiga toxin-producing Escherichia coli (STEC) represent clinically important human foodborne pathogens. The presence, transmission, and molecular epidemiology of these pathogens in primary agricultural environments (i.e., grazing pastures and produce farms) is understudied and represents a significant knowledge gap. We conducted a two year longitudinal sampling study in Northern Colorado to assess the presence, genetic diversity, and potential transmission patterns of these pathogens in production agriculture environments. Five produce farms and five grazing pastures in Northern Colorado were selected and sampled during the spring, summer, and fall in 2009 and 2010. Microbiological analysis was performed on composite soil (228 samples), composite fecal (105 samples), composite water (80 samples), and individual drag swabs (227 samples) to detect Listeria (i.e., L. monocytogenes and other Listeria spp.), Salmonella, E. coli O157:H7, and non-O157 STEC. Samples were evaluated to detect each target organism using modified versions of the U.S. Food and Drug Administration Bacteriological Analytical Manual and presumptive colonies for each target organism were confirmed by PCR. Overall, eight (1.25%), eleven (1.7%), and 22 (3.4%) of samples tested positive for L. monocytogenes, Salmonella, and STEC, respectively. Thirty-one samples contained Listeria spp. other than L. monocytogenes, the majority of which were determined to be Listeria innocua by sigB allelic typing. Additionally, 20 samples were positive for a proposed novel Listeria spp. that displayed unique phenotypic traits, i.e., non-motility and impaired growth at 37oC. Pulse field gel electrophoresis analysis indicated isolates obtained in this study to exhibit significant genetic diversity. These results demonstrate a rare presence of foodborne pathogens in agricultural environments in Northern Colorado. Prevalence and molecular subtyping data generated by this study provides important insight into the molecular epidemiology of these pathogens in the pre-harvest agriculture environment. Listeria monocytogenes uses the key virulence factor internalin A (InlA; encoded by inlA) to traverse host cell barriers during establishment of a systemic infection. Multiple naturally occurring mutations leading to a premature stop codon (PMSC) in inlA have been reported worldwide, and these mutations have been shown to be virulence attenuating in guinea pig infection models. Ribotype DUP-1039C is a broadly distributed molecular subtype within L. monocytogenes that has been commonly isolated along the food continuum. Ribotyope DUP-1039C isolates have been shown to carry three distinct PMSC mutations in inlA, including a frameshift mutation in a 5' homopolymeric tract of adenine restudies (PMSC4), a C to T substitution leading to a PMSC at aa 562 (PMSC 7), and a G to A substitution leading to a PMSC at aa 684 (PMSC 12). Additionally, DUP-1039C isolates carry one of three allelic types of a 5' hypermutable region of inlA, which may have a role in phase variation. A selection of DUP-1039C isolates available from the PathogenTracker database (n=368) were screened for known inlA PMSCs and the allelic type of the 5' hypermutable region by two multiplex single nucleotide polymorphism (SNP) genotyping assays. SNP genotyping assays included (i) a previously described single nucleotide extension assay and (ii) a newly developed probe-based assay, which uses differentially labeled probes to differentiate between wild type (WT; AAAAAAA), frameshift (FS; AAAAAA), and interrupted HT (IHT; AAGAAAA) 5' allelic types of inlA. DUP-1039C isolates carrying a PMSC in inlA were not uniformly distributed among isolation sources. inlA PMSC type 4 (n=19) and PMSC type 7 (n=25) were associated (P < 0.05) with isolation from food and food environments, while WT isolates encoding a full-length InlA (n=184) were associated (P < 0.05) with non-food environments and mammalian hosts. Interestingly, all DUP-1039C isolates carrying inlA PMSC7 also had the IHT inlA allele in the hypermutable 5' region, and these isolates persisted within a single NY state seafood processing plant. The 5' IHT allelic type was frequently encountered among isolates from diverse sources, though at lower frequencies as compared to the WT allele. Together, the results may help to explain the underlying mechanisms behind the ability of lineage II L. monocytogenes isolates to adapt to both human and environmental niches.
Keywords: environmental; foodborne; food safety; microbiology; pathogens; sampling